Is It Possible to Use Biodiesel as a Reference Material? - Filho, Dalni Malta do E. Santo; Siqueira, José Renato R.; Borges, Renata Martins H.; Rodrigues, Claudio Roberto da C.; Barbosa, Alex Pablo F.; Júnior, José Júlio P. dos Santos; Pereira, Roberto G. (IntechOpen, 2011)
None